LEGAL ASSESSMENT OF RUSSIAN CRIMES IN UKRAINE - Andrukhiv O. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. The purpose of our research is to form a legal assessment of Russian war crimes in Ukraine, including on the basis of the historical retrospective of human rights violations that took place in the Soviet era. Method. The methodology includes the complex use of scientific approaches and principles, as well as general scientific, philosophical and special scientific methods. Results. It was established that during the more than ten-year period of Russia's military aggression against Ukraine, many violations in the field of international law were committed, related to the violation of human rights and international humanitarian law. Many of these violations can be equated to war crimes and crimes against humanity. Among them, deliberate killings of both civilians and prisoners of war occupy an important place. In our opinion, it is worth paying attention to the most revealing «war crimes» committed by Russia in Ukraine and which require its prosecution, namely the deportation of minors; execution of prisoners of war; the crime of ecocide; mass killings and abuse of the civilian population. It was established that the national legislation does not provide for the definition of «war crimes» at all and operates only with the concept of «war crimes», which does not fully reflect the essence of the problem. As a result, it is now necessary not only to harmonize the norms of national and international legislation in the context of defining the content of such types of crimes as war crimes, crimes against humanity and the crime of aggression, but also to intensify the attention of international institutions responsible for their investigation. Scientific novelty. An analysis of national legislation on the qualification of war crimes committed and committed by Russia in Ukraine was carried out. Practical significance. The results of the research can be used in further historical and legal studies, preparation of special courses.